An analysis of the physical demands of international female soccer match-play and the physical characteristics of elite players - Datson, N. (Liverpool John Moores University, 2016)
The purpose of the thesis was to provide a detailed analysis of the physical demands of competitive international female soccer match-play and the physical characteristics of elite players. To date, the majority of research has focussed on sub-elite players with a lack of information available on international level competitors. The aim of the first study (Chapter 4) was to analyse match physical performance using a computerised tracking system (Prozone Sports Ltd., Leeds, England). A total of 167 individual match observations from 122 players competing in competitive international matches during the 2011-2012 and 2012-2013 seasons were completed. Total distance and total high-speed running distances (>14.4 km.h-1) were influenced by outfield playing position, with central midfielders completing the highest (10985 ± 706 m and 2882 ± 500 m) and central defenders (9489 ± 562 m and 1901 ± 268 m) the lowest distances, respectively. Greater total very high-speed running distances (>19.8 km.h-1) were completed when a team was without (399 ± 143 m) compared to with (313 ± 210 m) possession of the ball. The majority of sprints (>25.1 km.h-1) were over short distances with 95 % being less than 10 m. This study provides novel findings regarding the physical demands of different playing positions in competitive international female match-play and important insights for physical coaches preparing elite female players for competition. The aim of the second study (Chapter 5) was to determine the incidence and nature of repeated sprint and high-speed activity in match-play. Repeated sprint activity (a minimum of two efforts (>25.1 km.h-1) with 20 s or less recovery between efforts) was found to be rare during international female match-play with 1.1 ± 1.1 bouts per match. Repeated high-speed activity (a minimum of two efforts (>19.8 km.h-1) was influenced by playing position; with attacking-based players completing more bouts (37-40 bouts per match) than defensive players (22-33 bouts per match). Repeated sprint and high-speed bouts frequently comprised two efforts per bout, with a maximum of three and six efforts respectively. Collectively, this study provides physical coaches with useful data for replicating the demands of repeated high-speed activity and an understanding of the positional demands in order to aid the specificity of training. The aim of the third study (Chapter 6) was to attempt to apply a suitable approach for determining speed zones and to evaluate the application of specific zones to influence data outcome. Maximum match-play running speed in elite females was measured using Global Positioning System technology (STATSports, Viper, Ireland) in 230 individual match observations of 67 outfield players, during 19 international matches from 2011-2015. Female-specific speed zones and activity classifications were scaled appropriately to maximum match-play running speed. The resultant female-specific speed zones were on average 12.5 % lower than the standardised male zones, which if applied to the data in Chapter 4 would result in a small increases in total high-speed running (25 % to 28 %) and total very high-speed running (8 % to 9 %) relative to total distance. The calculated female-specific sprinting threshold (>22.0 km.h-1) corresponds to 82 % of the average maximum female match-play running speed presently observed and consequently might be more representative than the standardised male sprinting threshold (>25.1 km.h-1). However, as it was not possible to validate activity classifications in the current study it is suggested that the standardised thresholds should continue to be used to permit between playing position and gender comparisons, however, the activity classifications (e.g. walking, jogging, sprinting etc.) should be removed and replaced with the actual velocities. The aim of the fourth study (Chapter 7) was to examine the reliability of both anthropometric and performance measures in elite female soccer players. The data suggest that both junior and senior elite female players are able to adequately reproduce a variety of anthropometric (coefficient of variation = 0.1-1.3 %) and performance (coefficient of variation = 0.6-7.7 %) related tests and that reliable measures can be obtained using the present protocols and one familiarisation session. The sample size estimations (n<20) provided important insights for the participant recruitment in Chapter 8 and also suggest that the anthropometric and performance assessments are suitable for the longitudinal tracking of the fitness status of elite female players. The aim of the fifth study (Chapter 8) was to examine the physical characteristics of elite players, which were assessed in 471 national team players from 2011-2015. Anthropometric and performance variables improved with age; with large differences observed between U15s and seniors for body mass (53.9 ± 7.8 v 62.5 ± 5.8 kg), 30 m linear speed (4.78 ± 0.22 v 4.52 ± 0.17 s), countermovement jump (28.3 ± 4.0 cm v 33.4 ± 4.0 cm) and Yo Yo Intermittent Recovery Test Level 1 (1101 ± 369 m v 1583 ± 416 m). Similarities were observed for anthropometric and performance variables between the younger (U15 and U17) and older (U19 and senior) age groups. Goalkeepers generally exhibited inferior anthropometric and performance capabilities to outfield players. Faster linear speed times over short distances observed were in attackers (1.047 s v 1.061-1.077 s), greater repeated speed performance in wide midfielders and attackers (4.89-4.91 s v 4.92-4.99 s) and improved intermittent endurance performance in wide defenders (1483 m v 1260-1336 m) compared to other outfield playing positions. The normative physical characteristics presented, provide unique data for professionals involved in player recruitment and talent identification, whilst the positional differences in performance characteristics, coupled with an in-depth understanding of the demands of match-play can be applied to ensure training specificity. Collectively, the present data provides the most in-depth description of the physical demands and physical characteristics of elite female soccer players to date. The data describing the demands of match-play provides valuable insights for physical coaches preparing elite female players for competition, whilst the normative physical characteristic data provides important information to professionals involved in player recruitment and talent identification and those responsible for physical development.